PEMEROLEHAN SINTAKSIS PADA ANAK USIA DINI - Fitriyah, Tika; Firdausah, Isyqie (Universitas Muhammadiyah Tapanuli Selatan, 2023)
Language and humans are two inseparable entities. Both of them influence each other. The purpose of the study is to reveal the acquisition of syntax that occurs in early childhood. This research is significant because the development of language acquisition in children changes over time. This research is descriptive-qualitative, the methods used in data collection are questionnaires, interviews, and documentation. The participants of this study were early childhood children in the Special Region of Yogyakarta. The results of this study indicate that children aged 1-2 years can talk in the form of one word, children aged 2-3 years can talk in the form of two words, three words, even some of them can pronounce sentences with the right syntactic arrangement, namely subject + predicate and object, while children aged 3 years and up can talk in complete sentences. Children 3 years old and up can talk using declarative, imperative, and interrogative sentences. The result of the study indicates that children's habit of watching television or playing gadgets for more than 4 hours a day have a delay in talking.